Consumers of Higher Education in Australia : do the unfair contract term provisions in the Australian Consumer Law provide effective protection for students as consumers of educational services? - Goldacre, Lisa A. (Curtin University, 2012)
Extensive consumer protection legislation has existed in Australia for nearly four decades. The new Australian Consumer Law (‘ACL’) in schedule 2 of the Competition and Consumer Act 2010 (Cth) (‘CCA’)1 is the most significant change to consumer rights since the introduction of the Trade Practices Act 1974 (Cth) (‘TPA’). Over a corresponding period of time, the landscape of the higher education sector has been transformed into a culture of consumerism with the student at the centre as the consumer. However, students have seldom sought redress in relation to infringement of their rights as consumers under consumer protection legislation and more rarely successfully. It is recognised that some rights do accrue to students as consumers of educational services under the ACL, principally with regard to promotional activities of higher education institutions (‘HEI’).2 It is not certain that the ACL can provide effective protection for students as consumers of educational services beyond this known application to address issues regarding the nature of the service provided. This research is specifically concerned with whether the introduction of an Unfair Contract Terms (‘UCT’)3 regime in the ACL overcomes identifiable barriers faced by students using consumer protection as a means to ensure they receive services as promised and advances their rights as consumers.The ACL saw the introduction of an UCT regime, which previously had only existed in limited jurisdictions in Australia, notably Victoria, as a means of protection in consumer contracts. Now any term in a consumer contract that is an unfair term as defined under the ACL is void. The application of these provisions in the context of the student as a consumer of educational services will require first an assessment of whether there exists in Australia a contract between the student and HEI. Further, for the UCT to apply, the student–HEI contract must be a ‘standard form’ ‘consumer contract’4, for ‘services’ occurring in ‘trade or commerce’5. Importantly the analysis will identify any connection between the UCT provisions regarding substantive unfairness and the protection this affords students in the context of the provision of educational services, such as the design and delivery of courses, as distinct from promotional activities.Ordinarily, claims concerned with the nature of the educational service provided are considered matters that involve questions of academic judgement. Courts have been consistent in their reluctance to examine matters relating to the exercise of academic judgement and accordingly such matters are considered non-justiciable. The significance of the UCT provisions is that rather than just focusing on procedural unfairness, they attempt to deal with substantive unfairness.6 In the context of the student–HEI contract and provision of educational services, the UCT provisions have the potential to ensure that the student–HEI contract does not contain terms that are substantively unfair. Consequently, HEIs may now be obliged to provide educational services in a manner students might reasonably expect upon entering the student– HEI contract. Thus the new UCT regime may deal with claims concerning the provision of educational services more effectively than other actionable rights that require the court to examine matters of academic judgement in relation to the nature of educational services provided. The analysis will evaluate the implications for the higher education sector and make recommendations for change in the current practice.